Rationale, design, and baseline characteristics of ARTS-DN: a randomized study to assess the safety and efficacy of finerenone in patients with type 2 diabetes mellitus and a clinical diagnosis of diabetic nephropathy - Ruilope, Luis M.; Agarwal, Rajiv; Chan, Juliana C.; Cooper, Mark E.; Gansevoort, Ron T.; Haller, Hermann; Remuzzi, Giuseppe; Rossing, Peter; Schmieder, Roland; Nowack, Christina; Ferreira, Anna C.; Pieper, Alexander; et al. (American Journal of Nephrology, 2014)
Finerenone decreases albuminuria in patients having heart failure with reduced ejection fraction and mild-to-moderate (stage 2-3) chronic kidney disease. The MinerAlocorticoid Receptor Antagonist Tolerability Study-Diabetic Nephropathy (ARTS-DN; NCT01874431) is a multicenter, randomized, double-blind, placebo-controlled, parallel-group, phase 2b study. ARTS-DN investigated whether the mineralocorticoid receptor antagonist finerenone reduces albuminuria without causing major alterations in serum potassium levels in patients with type 2 diabetes mellitus and a clinical diagnosis of DN who were receiving a renin-angiotensin-system (RAS) inhibitor.Patients were randomized to oral finerenone 1.25-20 mg or placebo once daily. The primary objectives were to assess the ratio of the urinary albumin-to-creatinine ratio at day 90 to that at baseline in patients receiving finerenone, and to compare it with that in the placebo group. Additional exploratory analyses included evaluating changes from baseline in serum potassium levels, efficacy and safety biomarkers, and health-related quality of life.Of 1,501 patients screened, 821 (the sample population) received at least one dose of finerenone/placebo. Baseline characteristics included: male, 77.8%; white, 84.2%; very high albuminuria (formerly macroalbuminuria), 38.4%; high albuminuria (formerly microalbuminuria), 60.3%; median (range) estimated glomerular filtration rate, 66.3 (24.5-130.7) ml/min/1.73 m(2); and systolic blood pressure (mean ± standard deviation), 138.1 ± 14.4 mm Hg. There was a history of cardiovascular disease in 39.6%, diabetic neuropathy in 20.0%, and diabetic retinopathy in 19.9% of patients.ARTS-DN is the first phase 2b trial of finerenone in combination with a RAS inhibitor in patients with type 2 diabetes mellitus and a clinical diagnosis of DN.
EVALuna2:3938